Review on the influence of process parameters in incremental sheet forming - Gatea, Shakir; Ou, Hengan; McCartney, Graham (Springer, 2016)
Incremental sheet forming (ISF) is a relatively new flexible forming process. ISF has excellent adaptability to conventional milling machines and requires minimum use of complex tooling, dies and forming press, which makes the process cost-effective and easy to automate for various applications. In the past two decades, extensive research on ISF has resulted in significant advances being made in fundamental understanding and development of new processing and tooling solutions. However, ISF has yet to be fully implemented to mainstream high-value manufacturing industries due to a number of technical challenges, all of which are directly related to ISF process parameters. This paper aims to provide a detailed review of the current state-of-the-art of ISF processes in terms of its technological capabilities and specific limitations with discussions on the ISF process parameters and their effects on ISF processes. Particular attention is given to the ISF process parameters on the formability, deformation and failure mechanics, springback and accuracy and surface roughness. This leads to a number of recommendations that are considered essential for future research effort.